Oral administration of angiotensin-(1-7) ameliorates type 2 diabetes in rats - Santos, Sérgio H. S. (2014)
Diabetes mellitus type 2 (DM2) is a disease with increasing importance in modern societies and insufficient treatment options. Pharmacological stimulation of insulin signaling, which is blunted in DM2, is a promising approach to treat this disease. It has been shown that activation of the angiotensin (Ang)-(1-7)/Mas axis of the renin-angiotensin system leads to an improved glucose uptake. In this study, we intended to evaluate, whether this effect could be exploited therapeutically. We first confirmed that Ang-(1-7) improves insulin signaling and glucose uptake in vitro in cultured cardiomyocytes. We then evaluated the therapeutic effect of a newly developed hydro-xypropyl- β-cyclodextrin-based Ang-(1-7) nano-formulation in a novel transgenic rat model of inducible insulin resistance and DM2. The chronic administration of this compound prevented the marked elevation in blood glucose levels in these rats at a dose of 30 μg/kg, reversed the established hyperglycemic state at a dose of 100 μg/kg, and resulted in improved insulin sensitivity, reduced plasma insulin and decreased diabetic nephropathy. In conclusion, an oral Ang-(1-7) formulation reverses hyperglycemia and its consequences in an animal model of DM2 and represents a novel therapeutic option for the treatment of DM2 and other cardio-metabolic diseases. Key message: A novel rat model with inducible diabetes can be used to evaluate new therapies. Angiotensin-(1-7) is effective in an oral formulation packaged in cyclodextrine. Angiotensin-(1-7) is a promising antidiabetic drug.